Nuclear Expression of β-Catenin Is Associated with Improved Outcomes in Endometrial Cancer - Valeria Masciullo; Tommaso Susini; Giacomo Corrado; Marina Stepanova; Alessandro Baroni; Irene Renda; Francesca Castiglione; Corrado Minimo; Alfonso Bellacosa; Benito Chiofalo; Enrico Vizza; Giovanni Scambia (Diagnostics, 2022)
Beta-catenin is involved in intercellular adhesion and participates in the Wnt signaling pathway. This study evaluated the expression pattern and prognostic value of β-catenin in a series of endometrial carcinoma patients. Immunohistochemical analyses were used to assess the expression and subcellular localization of β-catenin from tissue sections of 74 patients with endometrial carcinoma. No correlation was found between beta-catenin expression and clinicopathological parameters. Patients expressing nuclear β-catenin (n = 13; 16%) showed a more favorable prognosis than patients expressing membranous β-catenin; the 5-year disease-related survival rate was 100% for cases expressing nuclear β-catenin, compared with 73.8% (SE 0.08) of cases expressing membranous β-catenin (p = 0.04). Although statistical significance was not reached (p = 0.15), cases expressing nuclear β-catenin showed a 5-year disease-free survival rate of 90.9% (SE 0.08) compared with 67.4% (SE 0.08) of cases expressing membranous β-catenin. Univariate Cox analysis revealed that membranous β-catenin expression was found to be associated with a relative risk of death of 33.9 (p = 0.04). The stage of disease (p = 0.0006), histology (p = 0.003), and grading (p = 0.008) were also significantly correlated with disease-free survival according to univariate Cox analyses. Determining β-catenin expression and localization patterns may predict survival in patients with endometrial cancer and, therefore, should be considered a potential prognostic marker of disease.